Development Of E-Book On The Implementation Of Differentiated Learning For Chemistry Teachers - Herman, Mimi; Fathia, Wilda; Herman, Hidayat; Rahmi, Elvy (Universitas Lampung, 2024)
Various education problems in Indonesia such as learning crises, learning loss, and the low PISA ranking in 2022 require a concrete solution. One of the efforts is through the implementation of the independent curriculum since 2021. In realizing these efforts, the Independent Curriculum carries a student-oriented learning paradigm which is implemented differentiated learning. However, the fact encountered is that there are still many teachers who do not understand how to carry out differentiated learning. The purpose of this study is to find out the validity of the E-book Guidelines for the Implementation of Differentiated Learning for Teachers in Chemistry Learning Phase E of High School/MA Equivalent by using a 4D development model consisting of Define, Design, Develop and Deseminate. The instrument used is a validity questionnaire. The validity tested includes the validity of the content (chemistry and differentiated learning), graphics and language. The data collection technique is carried out by distributing questionnaire instruments and practicality sheets that have been valid. The data was analyzed by processing alternative answers contained in the questionnaire and then transformed into quantitative data to obtain interval data using the kappa moment. The results obtained were the validity of the chemistry content with a value of 0.7365 with a valid category, the validity for differentiated learning content with a value of 0.87 with a very valid category.Based on the results of the research and discussion, it can be concluded that the development of E-Book on The Implementation of Differentiated Learning for Chemistry Teachers is valid and very feasible to be used in learning activities.Keywords: chemistry, differentiated learning, e-book.DOI: 10.23960/jppk.v13.i3.32793